Early platelet elevation after complete remission as a prognostic marker of favourable outcomes in favourable‐ and intermediate‐risk acute myeloid leukaemia: A retrospective study. Issue 2 (3rd January 2022) - Wen, Xiaoling; Li, Ruoqi; Zhang, Xialin; Zhai, Jiahong; Yang, Suxia; Wang, Yaozi; Tan, Yanhong; Xu, Zhifang; Yang, Linhua; Zhang, Ruijuan
Abstract: Objectives: Platelet (PLT) recovery after chemotherapy is associated with the prognosis of patients with acute myeloid leukaemia (AML). This study aimed to explore the prognostic significance of early high PLT values in patients with de novo non‐M3 AML who achieved first complete remission (CR). Methods: A total of 206 patients with de novo non‐M3 AML were analysed in this retrospective study. A receiver operating characteristic (ROC) curve was used to determine the optimal PLT cut‐off. The overall survival (OS) and relapse‐free survival (RFS) were assessed using Kaplan‐Meier and Cox regression analyses. Results: 312×10 9 /L was confined as the cut‐off of the PLT count. The estimated 3‐year OS of patients with high PLT was higher than that of their counterparts (72.3% vs. 34.6%, p = 0.001). In subgroup analysis, patients with high PLT had better OS in the favourable‐ and intermediate‐risk (non‐adverse‐risk) AML ( p = 0.001). The estimated 3‐year RFS for the high and low PLT groups was 75.1% and 45.7% respectively ( p = 0.078). Multivariate analyses revealed that high PLT count was an independent favourable variable for OS (HR = 0.264, p < 0.001) and RFS (HR = 0.375, p = 0.011) in the non‐adverse‐risk group. Conclusion: Our results showed that early high PLT count recovery at first CR in non‐adverse‐risk AML patients is a positive prognostic marker for survival outcomes. Abstract : Our study showed that early high PLT count recovery at first CR in non‐adverse‐risk AML patients is a positive prognostic marker for survival outcomes.